THE STATE DEFENSE RELATED TO THE OPERATION OF UNMANNED AERIAL VEHICLE (UAV) BY THE INDONESIAN NAVY - Dwika Tahja Setiawan; Anton Nugroho; Azi Wardiana (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
Indonesia as an archipelagic state with its geostrategic location which at the same time has the potential for economic, cultural, security and defense threats. Defense for a country is a fundamental need since independence and its existence against the struggles of the international world. The need for national defense occurs because of a threat that comes from a foreign country or certain organization against the existence of the state, territorial sovereignty and national safety. It is stated that the nature of national defense is all defense efforts that are universal in nature, carried out with awareness of the rights and obligations of the state and belief in one's own strength. This research is a descriptive study using qualitative methods, where data and information related to research problems obtained through literature studies and field interviews are analyzed qualitatively, and then interpreted according to the meaning contained in the data and information. The operation of UAVs by the Indonesian Navy in carrying out national defense uses several principles, namely the pilotless principle, the principle of state sovereignty, the principle of aviation security and safety, the principle of responsibility and the principle of the right to human privacy, but do not yet have the power and legal certainty to regulate their use for the benefit of the Indonesian Armed Forces. Sea. So that’s why In order to increase the strength and capability of the Marine Defense Weapon System Main Tool, it is necessary to disseminate and master international and national legal aspects to the crew so that in operation they do not violate the law and do not harm other people and flight safety. Keywords: Indonesian Navy, Unmanned Aerial Vehicle (UAV), and Marine Defense.